Perception of nurses about the risk assessment of the low complexity non-referred user - Buriola, Aline; Silva, Camilla Passarela; Cazanas, Eduardo Fuzetto; Nascimento, Tayomara Ferreira [UNESP] (Univ Estadual Maringa, Pro-reitoria Pesquisa Pos-graduacao, 2020)
The goal of this study was to assess the perceptions and behaviors of nurses who provide triage with risk assessment to low complexity non-referred patients. The participants of the study were nurses who were performing patients' triage with risk assessment, and the sample consisted of thirteen participants. The instruments used for the interviews were semi-structured questionnaires related to the characterization of the topic under study. Content analysis, i.e., the method proposed by Bardin, was used for data analysis. For data organization, we used MAXQDA Analytics Pro 2018, a software program that favored the identification between the similarities of the elements and ideas, thus making it possible to reach the cores of meanings. The identified categories were: (a) understanding about the healthcare provided by the emergency/urgency care Network; (b) evaluation of patient triage with risk classification; and (c) difficulties/challenges observed at the institution when providing user assessment with risk classification. It is concluded that nurses' perceptions regarding the topic under study were linked to the disarticulation of the healthcare Network, the fragility of the relationship between physicians and nurses, and the lack of use of institutional protocols.
Keywords: emergency nursing; emergency hospital service; user assessment; triage